2012
DOI: 10.1073/pnas.1206846109
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous transmitter release recruits postsynaptic mechanisms of long-term and intermediate-term facilitation in Aplysia

Abstract: Whereas short-term (minutes) facilitation at Aplysia sensory-motor neuron synapses is presynaptic, long-term (days) facilitation involves synaptic growth, which requires both presynaptic and postsynaptic mechanisms. How are the postsynaptic mechanisms recruited, and when does that process begin? We have been investigating the possible role of spontaneous transmitter release from the presynaptic neuron. In the previous paper, we found that spontaneous release is critical for the induction of long-term facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…2 A and B). We chose that paradigm because it has been used most extensively to study postsynaptic mechanisms of facilitation in Aplysia (23,33,34), and we wished to investigate how those mechanisms are recruited (31). The results were generally similar to those for long-term facilitation, except that there was a larger decrease in the test-alone control EPSPs due to homosynaptic depression, which is quite reliable at these synapses at stimulation intervals of 10 min or less.…”
Section: Induction Of Long-term Facilitation Is Accompanied By Increamentioning
confidence: 70%
“…2 A and B). We chose that paradigm because it has been used most extensively to study postsynaptic mechanisms of facilitation in Aplysia (23,33,34), and we wished to investigate how those mechanisms are recruited (31). The results were generally similar to those for long-term facilitation, except that there was a larger decrease in the test-alone control EPSPs due to homosynaptic depression, which is quite reliable at these synapses at stimulation intervals of 10 min or less.…”
Section: Induction Of Long-term Facilitation Is Accompanied By Increamentioning
confidence: 70%
“…Previous evidence suggested that prolonged exposure to 5-HT may act to inhibit 5-HT receptor-coupled adenylyl cyclase (Sugita et al 1992(Sugita et al , 1997. One possible reason would be that enhanced spontaneous transmitter release during prolonged exposure to 5HT (Jin et al 2007(Jin et al , 2008) may activate presynaptic type II or III metabotropic glutamate receptors, which are negatively coupled to adenylyl cyclase. Consistent with that idea, an inhibitor of type II and III metabotropic glutamate receptors, LY341495 (1 mM), significantly enhanced facilitation by 10-min, 20 mM 5-HT (P , 0.05 compared with DMSO control overall) (Fig.…”
Section: Pre-and Postsynaptic Mechanisms Of Intermediate-term Facilitmentioning
confidence: 99%
“…One possibility is that the postsynaptic mechanisms are recruited in parallel with the presynaptic mechanisms by activation of pre-and postsynaptic 5HT receptors (Li et al 2005;Fulton et al 2008;Villareal et al 2007Villareal et al , 2009. Alternatively, recent studies have found that activation of presynaptic 5-HT receptors enhances spontaneous release of glutamate, which then activates metabotropic glutamate receptors to recruit the postsynaptic mechanisms of intermediate-term facilitation (Jin et al 2007(Jin et al , 2008 and initiate a cascade that may culminate in synaptic growth during long-term facilitation (Jin et al 2010). Those findings could explain why homosynaptic potentiation by tetanic stimulation of the presynaptic neuron (Jin and Hawkins 2003) involves some of the same postsynaptic mechanisms as intermediate-term Figure 2A1.…”
Section: Mechanisms Of Intermediate-term Facilitationmentioning
confidence: 99%
“…Submicromolar increments of [Ca 2ϩ ] increase asynchronous transmitter release from many synapses (Zucker and Regehr, 2002). There is growing evidence for functional physiological effects of asynchronous release at a variety of synapses (Chávez et al, 2006;Best and Regehr, 2009;Jin et al, 2012), including accessory mitral apical tuft (Castro and Urban, 2009).…”
Section: Introductionmentioning
confidence: 99%